1991
DOI: 10.1161/01.cir.83.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of atrial natriuretic peptide in human hypertrophic ventricle of hypertensive hearts and hearts with hypertrophic cardiomyopathy.

Abstract: To investigate the ventricular expression of atrial natriuretic peptide (ANP) in human hypertrophic hearts, we conducted an immunohistochemical study of 130 endomyocardial biopsy specimens obtained from the right side of the ventricular septum (RVB), left ventricular free wall (LVB), or both from a total of 80 patients: 44 patients with hypertrophic cardiomyopathy (HCM), 14 with apical hypertrophic cardiomyopathy (APH), 13 with hypertensive hearts (HHD), and nine without hypertrophy (controls). No patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Upregulation of ANF gene expression is a highly conserved genetic marker of ventricular hypertrophy both in vitro and in vivo. It occurs in response to a wide variety of hypertrophic stimuli and across highly divergent species (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Since the pattern of cardiac gene expression associated with ventricular hypertrophy is very similar to that observed in the embryonic heart, it has been hypothesized that similar mechanisms may mediate induction of the embryonic genes in both situations.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of ANF gene expression is a highly conserved genetic marker of ventricular hypertrophy both in vitro and in vivo. It occurs in response to a wide variety of hypertrophic stimuli and across highly divergent species (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Since the pattern of cardiac gene expression associated with ventricular hypertrophy is very similar to that observed in the embryonic heart, it has been hypothesized that similar mechanisms may mediate induction of the embryonic genes in both situations.…”
Section: Introductionmentioning
confidence: 99%
“…Takemura et al showed that, in a selected population of HCM patients, the ventricular ANP gene expresses in response to disease-specific changes (eg, myocardial fiber disarray, hypertrophy of myocytes and fibrosis) rather than as an adaptative response. 33 There might be unknown causes of the high plasma concentrations of ANP and BNP in some HCM patients and further studies are needed.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, ANP mRNA has been detected in the ventricles of patients with HCM. 33 Thus, the high plasma concentrations of ANP detected in HCM patients may have originated mainly from the left ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this we note that the ventricular ANP mRNA level in THM was approximately 40-fold higher than that in normotensive mice, and corresponded with an increase in ventricular ANP concentration. ANP is also synthesized in the working myocytes in the ventricle of a hypertensive heart [2,31], a heart with hypertrophic cardiomyopathy [33,38] and in heart failure [43] as the urgent circulating hormone. The manner of the secretion of ANP in the diseased heart may be associated with some augmented biosynthesis of ANP in the ventricular cardiocytes.…”
Section: Discussionmentioning
confidence: 99%